2000
DOI: 10.1128/mcb.20.9.3292-3307.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Pancreatic Islet-Specific GeneBETA2 (neuroD) by Neurogenin 3

Abstract: The BETA2 (neuroD) gene is expressed in endocrine cells during pancreas development and is essential for proper islet morphogenesis. The objective of this study is to identify potential upstream regulators of the BETA2 gene during pancreas development. We demonstrated that the expression of neurogenin 3 (ngn3), an islet-and neuron-specific basic-helix-loop-helix transcription factor, partially overlaps that of BETA2 during early mouse development. More importantly, overexpression of ngn3 can induce the ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
218
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(230 citation statements)
references
References 47 publications
11
218
0
1
Order By: Relevance
“…Our data demonstrate that without normal down-regulation of Neurog3, the β-cell population does not adequately expand and diabetes ensues. Interestingly, however, a very low level of Neurog3 expression persists in adult islets (30)(31)(32)(33). Recent studies demonstrated that this sustained low-level expression of Neurog3 contributes to endocrine function (33).…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that without normal down-regulation of Neurog3, the β-cell population does not adequately expand and diabetes ensues. Interestingly, however, a very low level of Neurog3 expression persists in adult islets (30)(31)(32)(33). Recent studies demonstrated that this sustained low-level expression of Neurog3 contributes to endocrine function (33).…”
Section: Discussionmentioning
confidence: 99%
“…The direct targets of Ngn3 include NeuroD1/ Beta2, Pax4, Arx, Insm1, Rfx6, Nkx2.2, Myt1, and Snail2/Slug (Huang et al, 2000;Smith et al, 2003Smith et al, , 2004Smith et al, , 2010Watada et al, 2003;Mellitzer et al, 2006;Wang et al, 2007;Rukstalis and Habener, 2007;Soyer et al, 2010) (Fig. 2B).…”
Section: Endocrine Specificationmentioning
confidence: 99%
“…This class of factors also permits endocrine cells to move into the mono-hormone-producing cell state. Several TF genes that fall into this category [e.g., NeuroD1 (Huang et al, 2000), Insm-1, Rfx6, and Islet1] are downstream, primarily direct targets, of Ngn3. NeuroD mutant mice have arrested endocrine cell development during the secondary transition, with reduced numbers of all endocrine cell types.…”
Section: Class I: General Endocrine Precursor Differentiation Factorsmentioning
confidence: 99%
“…The transcriptional activity of BETA2 (NeuroD) in NSCs was determined by the BETA2 promoter-luciferase reporter plasmid kindly provided by Dr Ming-Jer Tsai (Baylor College of Medicine, Houston, TX, USA) (Huang et al, 2000). Cells were plated at a density of approximately 5 Â 10 4 cells/ml, transfected with the luciferase reporter plasmids (1 mg each) using Fugen 6 transfection Reagent (Roche Applied Science) according to the manufacturer's instruction, cultured overnight and irradiated.…”
Section: Luciferase Assaymentioning
confidence: 99%